Crystal plasticity analysis of cylindrical holes and their effects on the deformation behavior of Ni-based single-crystal superalloys with different secondary orientations. (August 2019) - Zhou, Hui; Zhang, Xiao; Wang, Pei; Lu, Shanping
Abstract: The effects of cylindrical holes and secondary orientations on the deformation behavior of Ni-based single crystals were investigated by in-situ tensile experiments and crystal plasticity simulations using models based on dislocation density evolution. In the experiments and simulation, a load was applied along [001] (primary orientation), while the holes were prepared along two different secondary orientations: [100] (orientation A) and [110] (orientation B). We obtain excellent agreement between simulation and experiments and reveal that the addition of hole induces multi-axil stress condition in the single crystal sample, which facilitates the plastic deformation and promotes anisotropic plastic deformation around hole. For specimen with three holes, the interaction among the holes induces plastic slip in some areas, which enhances the plastic slip in the regions adjacent to the side holes and inhibits the plastic slip in the regions around central hole. Therefore, the plastic deformation around the side hole demonstrates unsymmetrical features, and the plastic deformation around the side hole is larger than that around the central hole, which preferentially induces cracks. The secondary orientations influence the activities of the slip systems. Compared to the specimens with orientation B, more slip systems are activated and the plastic slips are homogeneous for specimens with orientation A; therefore, the fracture strains and tensile strengths of the specimens with orientation A are higher than those of the specimens with orientation B. Highlights: The results of CPFEM based on dislocation evolution agree with in-situ experiments results. The addition of hole(s) promotes the heterogeneous plastic deformation behaviors. The holes' interactions induce larger plastic strain around side hole and initiate cracks. Hole and secondary orientation have synthetic effects on the deformation behaviors. With the help of holes, secondary orientation changes activities of slip systems.